2003
DOI: 10.1007/s00122-003-1450-6
|View full text |Cite
|
Sign up to set email alerts
|

Medicago truncatula EST-SSRs reveal cross-species genetic markers for Medicago spp.

Abstract: Expressed sequence tags (ESTs) are important resources for gene discovery and molecular marker development. From over 147,000 ESTs of Medicago truncatula, we have identified 4,384 ESTs containing perfect simple sequence repeats (EST-SSR) of di-, tri-, tetra- or pentanucleotides. Six hundred sixteen primer pairs (PPs) were designed and screened over a panel of eight genotypes representing six Medicago spp. and subspecies. Nearly, 74% (455) of the PPs produced characteristic SSR bands of expected size length in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

24
151
2
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 259 publications
(183 citation statements)
references
References 29 publications
24
151
2
2
Order By: Relevance
“…In earlier reports, tri-nucleotide repeats were generally the most common motif found in both monocots [19] and dicots [17]. In the present investigation, tri-nucleotide repeat was also found to be the most abundant SSRs, followed by di-, tetra-, penta, and hexa-nucleotide (Table 1).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…In earlier reports, tri-nucleotide repeats were generally the most common motif found in both monocots [19] and dicots [17]. In the present investigation, tri-nucleotide repeat was also found to be the most abundant SSRs, followed by di-, tetra-, penta, and hexa-nucleotide (Table 1).…”
Section: Discussionsupporting
confidence: 79%
“…These two results indicated that the abundance of SSRs for sweetpotato ESTs was relatively higher than that for other species, e.g. peanut (6.8%) [30], barley (3.4%), maize (1.4%), rice (4.7%), soyghum (3.6%), wheat (3.2%) [31], Medicago truncatula (3.0%) [17], Epimudium sagittatum (3.4%) [32]. In this work, the frequency of occurrence for EST-SSRs was one EST-SSR in every 7.1 kb.…”
Section: Discussionmentioning
confidence: 99%
“…After controlling for inherent differences in variability from one locus to the next, however, it becomes clear that H. verticillatus actually harbors more genetic diversity than does H. angustifolius despite its rarity (Figure 1). Beyond providing more statistical power in paired comparisons, ESTSSRs also produce cleaner results for scoring as there are fewer null alleles (Leigh et al, 2003;Rungis et al, 2004) and fewer stutter bands (Leigh et al, 2003;Woodhead et al, 2003;Eujayl et al, 2004;Pashley et al, 2006). Despite these advantages, however, EST-SSRs are not without their drawbacks.…”
Section: Prospects and Pitfallsmentioning
confidence: 99%
“…With the rapid development of expressed sequence tags (ESTs), a large number of SSR markers have been developed from the ESTs library of Medicago truncatula (Baquerizo et al 2001;Eujayl et al 2004), a model diploid organism with 2n = 2x = 16. Eujayl et al (2004) searched 147,000 M. truncatula ESTs and identified 455 SSR primer pairs which produced characteristic SSR bands of the expected length in Medicago species.…”
Section: Introductionmentioning
confidence: 99%
“…Eujayl et al (2004) searched 147,000 M. truncatula ESTs and identified 455 SSR primer pairs which produced characteristic SSR bands of the expected length in Medicago species. Ellwood et al (2006) used six simple sequence repeat (SSR) loci to analyze the genetic diversity and relationships between randomly selected specimens from 192 accessions in the core M. truncatula collection.…”
Section: Introductionmentioning
confidence: 99%